Estimation of microbiological propagation and antimicrobial traits of the frequently accessible flowers - Sharmin, Marufa; Das, Kamal Kanta; Acharjee, Mrityunjoy (Stamford Journal of Microbiology, 2015)
Present study portrayed a complete microbiological profile of commonly available flowers including Rosa kordesii, Gladiolus hybrid, Acmella oleracea, Nyctanthes arbortristis and Pseudomussaenda flava which were randomly collected from Dhaka city, Bangladesh. The microbial contamination was quantified up to 108 cfu/g. Exploration of specific pathogenic bacteria was estimated within the range of 103 to 108 cfu/g of which Pseudomonas spp. was found in G. hybrid, A. oleracea and P. flava (~106 cfu/g), whereas Escherichia coli and Staphylococcal contamination was evident in almost all samples up to 108 cfu/g. The in vitro antimicrobial activities of the flower extracts were notable against most of the test bacteria. The ethanolic extracts of R. kordesii showed anti-bacterial activity against most of the bacteria except E. coli and Salmonella spp. G. hybrid extracts showed activity against Klebsiella spp. and Bacillus spp., A. oleracea against E. coli, Pseudomonas spp., Bacillus spp., Klebsiella spp., Staphylococcus spp. and Salmonella spp., P. flava against Pseudomonas spp. and Bacillus spp., and N. arbortristis against Bacillus spp. The methanol extracts of G. hybrid possessed activity against E. coli, Listeria spp. and Pseudomonas spp., N. arbortristis extracts against E. coli, Vibrio spp., Bacillus spp., Klebsiella spp. and Staphylococcus spp., P. flava extracts against E. coli. DOI: http://dx.doi.org/10.3329/sjm.v4i1.22756 Stamford Journal of Microbiology, Vol.4(1) 2014: 19-23